A Model of Anisotropic Property of Seepage and Stress for Jointed Rock Mass. (10th July 2013) - Wang, Pei-tao; Yang, Tian-hong; Xu, Tao; Yu, Qing-lei; Liu, Hong-lei
Abstract : Joints often have important effects on seepage and elastic properties of jointed rock mass and therefore on the rock slope stability. In the present paper, a model for discrete jointed network is established using contact-free measurement technique and geometrical statistic method. A coupled mathematical model for characterizing anisotropic permeability tensor and stress tensor was presented and finally introduced to a finite element model. A case study of roadway stability at the Heishan Metal Mine in Hebei Province, China, was performed to investigate the influence of joints orientation on the anisotropic properties of seepage and elasticity of the surrounding rock mass around roadways in underground mining. In this work, the influence of the principal direction of the mechanical properties of the rock mass on associated stress field, seepage field, and damage zone of the surrounding rock mass was numerically studied. The numerical simulations indicate that flow velocity, water pressure, and stress field are greatly dependent on the principal direction of joint planes. It is found that the principal direction of joints is the most important factor controlling the failure mode of the surrounding rock mass around roadways.